Dried blood spot omega-3 and omega-6 long chain polyunsaturated fatty acid levels in 7–9 year old Zimbabwean children: a cross sectional study. Issue 1 (December 2016) - Mashavave, Grace; Kuona, Patience; Tinago, Willard; Stray-Pedersen, Babill; Munjoma, Marshall; Musarurwa, Cuthbert
Abstract Background Omega-3 long chain-polyunsaturated fatty acids (LC-PUFAs)–docosahexaenoic acid (DHA), docosapentaenoic acid (DPA) and eicosapentaenoic acid (EPA)– and omega-6 LC-PUFA arachidonic acid (ARA), are essential for optimum physical and mental development in children. Prior to this study, the blood omega-3 LC-PUFA levels were unknown in Zimbabwean children, particularly in those aged 7–9 years, despite the documented benefits of LC-PUFAs. Documentation of the LC-PUFA levels in this age group would help determine whether interventions, such as fortification, are necessary. This study aimed to determine dried whole blood spot omega-3 and omega-6 LC-PUFA levels and LC-PUFA reference intervals among a selected group of Zimbabwean children aged 7–9 years old. Methods We conducted a cross sectional study from September 2011 to August 2012 on a cohort of peri-urban, Zimbabwean children aged 7–9 years. The children were born to mothers enrolled at late pregnancy into an HIV prevention program between 2002 and 2004. Dried whole blood spots were sampled on butylated hydroxytoluene antioxidant impregnated filter papers and dried. LC-PUFAs were quantified using gas liquid chromatography. Differences in LC-PUFAs between groups were compared using the Kruskal Wallis test and reference intervals determined using non-parametric statistical methods. Results LC-PUFAs levels were determined in 297 Zimbabwean children of whom 170 (57.2 %) were girls. The study determined that LC-PUFAs (wt/wt ) ranges were EPA 0.06–0.55 %, DPA 0.38–1.98 %, DHA 1.13–3.52 %, ARA 5.58–14.64 % and ARA: EPA ratio 15.47–1633.33. Sixteen participants had omega-3 LC-PUFAs levels below the determined reference intervals, while 18 had higher omega-6 LC-PUFAs. The study did not show gender differences in omega-3 and omega-6 LC-PUFAs levels (allp > 0.05). EPA was significantly higher in the 8 year age group compared to those aged 7 and 9 years (median; 0.20 vs 0.17 vs 0.18, respectively, p = 0.049). ARA: EPA ratio was significantly higher in the 7 year age group compared to those aged 8 and 9 years (median; 64.38 vs 56.43 vs 55.87 respectively, p = 0.014). Conclusions In this cohort of children, lower EPA levels and higher ARA: EPA ratios were observed compared to those reported in apparently healthy children elsewhere. The high ARA: EPA ratios might increase the vulnerability of these children to inflammatory pathologies. Identification and incorporation into diet of locally produced foodstuffs rich in omega-3 LC-PUFAs is recommended as well as advocating for dietary supplementation with omega-3 fish oils and algae based oils.